Impact From Social Media To Social Life - Eka Imama Novitasari; Ade Kurniawan; Yoga Dwi Goesty D.S; Arnes Yuli Vandika (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
As the easiest, cheapest and the largest place to show picture, sentence, and newest news, social media become the trend topic in our country. In the social media the users feel the freedom, but sometimes they can’t control their freedom until it become a disaster. Disaster for their social life and people around them. We need the education to educate them, how to manage their attitude in social media. This education will start from our children to cut the mistake in our society.